High performing smart electrochromic device based on honeycomb nanostructured h-WO3 thin films: hydrothermal assisted synthesis. Issue 6 (11th December 2014) - Kondalkar, Vijay V.; Mali, Sawanta S.; Kharade, Rohini R.; Khot, Kishorkumar V.; Patil, Pallavi B.; Mane, Rahul M.; Choudhury, Sipra; Patil, Pramod S.; Hong, Chang K.; Kim, Jin H.; Bhosale, Popatrao N.
Abstract : Honeycomb nanostructured single crystalline hexagonal WO3 (h-WO3 ) thin films in order to improve electrochromic performance. Abstract : Herein, we report honeycomb nanostructured single crystalline hexagonal WO3 (h-WO3 ) thin films in order to improve electrochromic performance. In the present investigation, honeycomb nanostructured WO3 with different unit size and nanowire array with highly nanocrystalline frameworks have been synthesized via a hydrothermal technique. The influence of hydrothermal reaction time on the honeycomb unit cells, crystallite size, lithium ion diffusion coefficient and switching time for coloration/bleaching were studied systematically. The electrochromic study reveals that the honeycomb unit cell size has a significant impact on the electrochromic performance. Small unit cells in the honeycomb lead to large optical modulation and fast switching response. A large optical modulation in the visible spectral region (60.74% at λ = 630 nm) at a potential of −1.2 V with fast switching time (4.29 s for coloration and 3.38 s for bleaching) and high coloration efficiency (87.23 cm 2 C −1 ) is observed in the honeycomb WO3 thin films with a unit cell diameter of 1.7 μm. The variation in color on reduction of WO3 with applied potential has been plotted on an xy -chromaticity diagram and the color space coordinate shows the transition from a colorless to deep blue state.